PENGARUH MODEL PEMBELAJARAN SAINS TEKNOLOGI MASYARAKAT (STM) TERHADAP AKTIVITAS BELAJAR DAN HASIL BELAJAR IPS SISWA - Wardinal, Lise; Miaz, Yalvema; Mayar, Farida; Irdamurni, Irdamurni (Jurnal Basicedu, 2019)
This type of research is a type of quasi-experimental research in the form of Random Research Group Control.The sample technique is Simple Random Sampling.The sample in this study was the experimental group class IV A using the Science Technology Community Learning Model (STM). Based on the results of the study showed that the model of Community Science Technology Learning (STM) affects the activities and learning outcomes in elementary schools that are tested and processed using t test.The results of the learning activity questionnaire before learning were obtained tcount = and the questionnaire test after learning were obtained tcount =. In addition, data showing pretest learning outcomes obtained tcount = with ttable = 2.024 and posttest learning outcomes tcount = with ttable = 2.024 at a significance level É‘ = 0.05. So it can be concluded that there is an influence of the Community Science and Technology Learning Model (STM) on the activities and learning outcomes of fifth grade students of SD 12 Padang Koto Gadang.